2021
DOI: 10.3171/2019.9.jns191949
|View full text |Cite
|
Sign up to set email alerts
|

An artificial intelligence framework for automatic segmentation and volumetry of vestibular schwannomas from contrast-enhanced T1-weighted and high-resolution T2-weighted MRI

Abstract: OBJECTIVEAutomatic segmentation of vestibular schwannomas (VSs) from MRI could significantly improve clinical workflow and assist in patient management. Accurate tumor segmentation and volumetric measurements provide the best indicators to detect subtle VS growth, but current techniques are labor intensive and dedicated software is not readily available within the clinical setting. The authors aim to develop a novel artificial intelligence (AI) framework to be embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
108
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 27 publications
0
108
2
2
Order By: Relevance
“…Deep learning is a sub-type of artificial intelligence that utilises multiple layers of analysis to process an image. A variety of applications of deep learning are postulated [ 7 , 20 , 42 ], and one study has shown this to be a useful approach in automated VS segmentation [ 32 ] in terms of both time and accuracy. Despite the accuracy of automated approaches, interactive corrections may continue to play a role even with deep learning due to the lack of adaptability of automated methods to the specific imaging sequences and protocols used clinically [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep learning is a sub-type of artificial intelligence that utilises multiple layers of analysis to process an image. A variety of applications of deep learning are postulated [ 7 , 20 , 42 ], and one study has shown this to be a useful approach in automated VS segmentation [ 32 ] in terms of both time and accuracy. Despite the accuracy of automated approaches, interactive corrections may continue to play a role even with deep learning due to the lack of adaptability of automated methods to the specific imaging sequences and protocols used clinically [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Automated segmentation may be accurate in the assessment of tumour progression and in overall survival prediction in glioma [1,26] as well as for the clinical assessment of biomarkers in glioma [4]. For VS imaging, automated segmentation has been applied with positive results [32,40] and there is growing interest in the field [10]. An automated segmentation tool could also improve clinical workflow and operational efficiency during the planning of stereotactic radiosurgery (SRS) by using the tool as an initialisation step in the process.…”
Section: Introductionmentioning
confidence: 99%
“…A major advantage of our method is that it is applicable to data from different scanners and institutions. Furthermore, curating a large sample of uniform images for deep learning training is time-and labour-intensive [28]. Even when training time is considered, use of our computer-assisted segmentation method can reduce annotation time by 20 min per patient compared to fully manual segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the largest studies investigating volumetric features and prognosis incorporating quantitative measurement of postoperative imaging and clinical variables. Future work to evaluate our approach should quantitatively compare segmentation measurements with manual segmentations from multiple observers to assess inter-rater variability [28]. In addition, an independent dataset is necessary for us to compare the relative prognostic performance of automated segmentations against manual segmentations and determine the reproducibility of our segmentations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, artificial intelligence has shown great potential in the application of medical imaging, especially the deep-learning model based on the neural network in the detection of diseases, segmentation, and quantitative evaluation of the lesions. [4][5][6][7][8] In this issue of the Journal of Magnetic Resonance Imaging, Pennig et al explored the performance of a deep-learning model (DLM) initially trained on gliomas to detect and segment PCNSL using multiparametric MRI at different field strengths from several imaging manufacturers, models, and study centers. 9 They used a DLM-based 3D convolutional neural network to achieve fully automated voxelwise segmentation of tumor components in a cohort of 43 patients with histologically proven PCNSL, which was compared to manual ground truth segmentations by two observers in contrastenhanced T 1 -weighted and fluid-attenuated inversion recovery images.…”
mentioning
confidence: 99%